2014
DOI: 10.1007/s12192-014-0507-6
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for a role of autoantibodies to heat shock protein 60, 70, and 90 in patients with dermatitis herpetiformis

Abstract: Heat shock proteins (Hsp) are highly conserved immunomodulatory molecules upregulated when cells are exposed to stressful stimuli, such as inflammation. Their involvement in various autoimmune diseases, including autoimmune bullous diseases and celiac disease, has been increasingly recognized. To further study the role of Hsp in autoimmune bullous diseases, we have investigated for the first time the humoral autoimmune response to Hsp40, Hsp60, Hsp70, and Hsp90 in patients with dermatitis herpetiformis (DH; n … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
38
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 37 publications
(41 citation statements)
references
References 29 publications
3
38
0
Order By: Relevance
“…In addition to the positive correlation between autoantibodies against Hsp90 and the cutaneous disease activity of DH patients, a positive relationship was observed between the humoral autoimmune response towards Hsp90 and the levels of circulating autoantibodies against eTG and tTG, which also fell during follow‐up. Similar observations were made for serum autoantibodies to Hsp60 and Hsp70 in this cohort of DH patients . As our previous studies mentioned above revealed only a low or similar expression of secreted (circulating) Hsp90 in patients with BP and PV, respectively , it is rather not surprising that these subgroups of autoimmune bullous disease patients had no increased humoral autoimmune response to this extracellular chaperone.…”
Section: Role Of Hsp90 In Autoimmune Bullous Diseasessupporting
confidence: 90%
See 1 more Smart Citation
“…In addition to the positive correlation between autoantibodies against Hsp90 and the cutaneous disease activity of DH patients, a positive relationship was observed between the humoral autoimmune response towards Hsp90 and the levels of circulating autoantibodies against eTG and tTG, which also fell during follow‐up. Similar observations were made for serum autoantibodies to Hsp60 and Hsp70 in this cohort of DH patients . As our previous studies mentioned above revealed only a low or similar expression of secreted (circulating) Hsp90 in patients with BP and PV, respectively , it is rather not surprising that these subgroups of autoimmune bullous disease patients had no increased humoral autoimmune response to this extracellular chaperone.…”
Section: Role Of Hsp90 In Autoimmune Bullous Diseasessupporting
confidence: 90%
“…The underlying molecular mechanism responsible for these observed B cell immunoregulatory effects of Hsp90 inhibition remains widely enigmatic. One explanation, however, could be derived from our observed finding of an increased expression of transcription factor heat shock factor 1 (17) and Hsp70 in stimulated human B cells treated with 17-DMAG, both of which are known to repress pro-inflammatory and activate anti-inflammatory genes (13).…”
Section: Introductionmentioning
confidence: 94%
“…HSP90 is a chaperone that assists other proteins for their correct folding. Antibodies against HSP90 have been detected in patients with DH , and their levels correlate with those of anti‐tTG antibodies. This suggests that the 33‐mer fragment may be able to bind to HSP90, and in some cases be attached to it by the cytosolic tTG, allowing the generation of autoantibodies.…”
Section: Extradigestive Manifestations In CD and Ncgs: Linking Diseasmentioning
confidence: 99%
“…Changes in serum levels of Hsp90 or anti-Hsp90 autoantibodies can be measured during the course of the disease and correlated to changes in disease activity. Such studies have been recently performed by us in patients with BP and dermatitis herpetiformis [24,26]. Unfortunately, the role of Hsp90 as drug target in MMP cannot be reasonably evaluated in the currently available in vivo murine models of MMP using passive transfer of subepidermal blister-inducing rabbit and human anti-laminin 332 IgG into neonatal/adult mice and human skin grafted onto immunocompromised adult mice, respectively [32,33], as well as rabbit or human anti-b4 integrin IgG into neonatal mice [34].…”
Section: The Hypothesis and Its Evaluation And Implicationmentioning
confidence: 99%
“…These include that (i) Hsp90 inhibitors exhibit activity in mice with experimental epidermolysis bullosa acquisita and in a respective ex vivo human dermal-epidermal separation cryosection model by potently affecting inflammatory disease pathways (i.e., inhibition of effector T cells, B cells, and neutrophils; suppression of autoantibody, proinflammatory cytokine, and reactive oxygen species production; promotion of regulatory B cells) [19][20][21], (ii) secreted basement membrane-degrading and blister-provoking matrix metalloproteinases with partly profibrotic potential are complexed by extracellular Hsp90 in sera of patients with epidermolysis bullosa acquisita, thus representing additional treatment targets of Hsp90 antagonists [21][22][23], (iii) Hsp90 is aberrantly expressed and secreted in the skin and blood of patients with BP, and its blockade modulates anti-BP180 autoantibody-induced production of proinflammatory IL-8 by cultured keratinocytes [24,25], and (iv) circulating autoantibodies to Hsp90 are elevated and positively correlated with disease activity and serum anti-epidermal/tissue transglutaminase autoantibodies in patients with dermatitis herpetiformis [26]. With regard to MMP, it has previously been reported that, in contrast to healthy persons and those with atopic keratoconjunctivitis, Hsp90 expression is upregulated in the conjunctival stroma and vasculature of patients with ocular disease [27].…”
Section: Introductionmentioning
confidence: 99%